LONGITUDINAL EVALUATION OF THE HEALTH-RELATED QUALITY OF LIFE IN COVID-19 PATIENTS: A COMPARISON BETWEEN PRE-INFECTION AND THREE MONTHS POST-DISCHARGE - Damjanovic, Radomir; Cvetković, Iva; Cvetanović, Maja; Milošević, Vuk; Stojanov, Aleksandar; Vojinović, Slobodan; Vrbić, Miodrag (Acta medicae Medianae, 2024)
The infectious disease COVID-19, caused by the SARS-CoV-2 virus, continues to be a significant global public health emergency. Alongside the undeniable effects on physical health, there is evidence of a serious impact on mental health as well. Our study aimed to assess changes in health-related quality of life in COVID-19 patients before hospitalization for SARS-CoV-2 infection and three months after discharge. Data were collected from 70 participants hospitalized for COVID-19. Participants were examined twice, after admission to the hospital and three months after discharge. Quality of life was measured with the 36-item Short Form Survey (SF-36), Pittsburgh Sleep Quality Index (PSQI), Patient Health Questionnaire-9 (PHQ9), and Generalized Anxiety Disorder 7-item (GAD-7). The statistical significance of two variables in the same sample at two distinct points in time was compared using a paired-sample T-test. There was a significant difference in PHQ9 scores before and after hospitalization (t = 4.738, p < 0.01). We found no significant change in PSQI score before hospitalisation or three months after discharge (t = -.622, p = 536). Our results showed a significant increase in GAD7 and a significant decrease in physical functioning (PF) (t = 5.929, p < 0.01) and role limitations due to physical health problems (RP) (t = 4.385, p < 0.01) scores. The findings indicate that there was no statistically significant difference between pre-infection and three months after discharge in the SF-36 questionnaire’s role limitations due to emotional problems (RE) and social functioning (SF) components. In summary, the results of our study suggest that COVID-19 patients have physical and mental health problems that may persist even after recovery and negatively affect their quality of life.